Serum immunoreactive cationic trypsinogen: a useful indicator of severe exocrine dysfunction in the paediatric patient without cystic fibrosis. Issue 11 (November 1986) - Moore, D J; Forstner, G G; Largman, C; Cleghorn, G J; Wong, S S; Durie, P R
Abstract : We evaluated serum cationic trypsinogen as a marker of exocrine pancreatic function in children without cystic fibrosis. The ability of this test to determine steatorrhoea of pancreatic origin, and its relationship to a wide range of exocrine pancreatic function were assessed. Serum trypsinogen was measured in 32 children with steatorrhoea, 10 with pancreatic and 22 with non-pancreatic causes. In patients with pancreatic steatorrhoea, serum cationic trypsinogen was 4.9 +/- 4.9 micrograms/l (mean +/- SD), significantly below values in patients with non-pancreatic steatorrhoea (47.0 +/- 22.1 micrograms/l, p less than 0.001) and 50 control subjects (31.4 +/- 7.4 micrograms/l, p less than 0.001). Serum cationic trypsinogen values in patients with pancreatic steatorrhoea all fell below the lower limit of our control range and below all values for patients with non-pancreatic steatorrhoea. Serum cationic trypsinogen was also evaluated against pancreatic trypsin output in 47 patients (range 0.2-17.0 yr who underwent a hormonal pancreatic stimulation test. In 17 patients, serum cationic trypsinogen was low (less than -2SD or less than 16.6 micrograms/l), and associated with greatly impaired pancreatic trypsin output, ranging from 0-8% of mean normal trypsin output. Five of these 17 patients did not have steatorrhoea. In 30 patients with normal or raised serum cationic trypsinogen (greater than or equal to 16.6 micrograms/l), pancreatic trypsin output ranged from 15-183% of mean normal values. In conclusion, low serum cationic trypsinogen suggests severely impaired exocrine pancreatic function, with sensitivity extending above the steatorrhoeic threshold. In the presence of steatorrhoea, low serum cationic trypsinogen indicates a pancreatic aetiology. Normal serum cationic trypsinogen, however, does not exclude impaired pancreatic function, above the steatorrhoeic threshold.